Physical examination and chemical analysis of erimin-5 tablets for forensic drug profiling - Mail, Radwan Mail (2021)
Seizure of illicit Erimin-5 drugs had been reported in Malaysia, indicating the seriousness of this issue. These drugs might contain nimetazepam or other substitutes that are classified under benzodiazepines. Benzodiazepines possess hypnotic and sedative effects, making them to be widely used as depressants on human central nervous systems. Due to potential of abuse, many benzodiazepines listed in the Schedule IV of the International Convention on Psychotropic Substances 1971 are banned in many countries, including Malaysia. In routine forensic analysis, gas chromatography-mass spectrometry (GC-MS) and high-performance liquid chromatography (HPLC) techniques are utilised for qualitative and quantitative determination of benzodiazepines, respectively. However, efforts on source tracking and sample-to-sample comparison of such illicit drug have not been prioritised thus far with only limited information could be retrieved for forensic intelligence. Therefore, forensic drug profiling of Erimin-5 tablets through physical and chemical means warrants further investigation with the aim to establish discrimination or clustering of these samples. In this study, 101 Erimin-5 tablets collected from case work were visually observed and evaluated in term of their shape, colour, diameter, thickness, and weight. Subsequently, the adulterants and colourants in the composition of Erimin-5 pills were determined using attenuated total reflectance-Fourier Transformed Infrared (ATR-FTIR) spectroscopy and thin layer chromatography (TLC), respectively. GC technique was also applied to confirm the presence of benzodiazepine related substances, and percentage of nimetazepam was quantified using HPLC. Through this study, physical examination demonstrated the unique characteristics of Erimin-5 tablets, allowing certain degree of sample-to-sample comparison. ATR-FTIR coupled with principal component analysis grouped the Erimin-5 samples into the clusters similar to those adulterated with mannitol or lactose. TLC analysis allowed the determination of possible colourants that had been added into the composition of these tablets, and in this study, mainly with sunset yellow dye. Through GC analysis, the Erimin-5 tablets were detected to have contained either nimetazepam or etizolam, where the former was scheduled under the Dangerous Drugs Act 1952. Nimetazepam was subsequently quantified using HPLC and reported with percentage range between 0.62 – 4.49%. To conclude, forensic discrimination of Erimin-5 samples was successfully carried out, at least allowing for sample-to-sample comparison. This study could benefit the law enforcement agencies through a series of physical and chemical examination strategies for illiciti drug related investigation and intelligence.